GENE-03. WILD-TYPE Tp53 UNDERGOES A CELL TYPE-SPECIFIC INACTIVATION BY SIRT1 IN DE NOVO GLIOBLASTOMA. (5th November 2018) - Li, Li; Vemireddy, Vamsidhara; Goodarzi, Mohammad; Mashimo, Tomoyuki; Billman, Tara; Hatanpaa, Kimmo; Mickey, Bruce; Maher, Elizabeth; Bachoo, Robert; Piccirillo, Sara
Abstract: In contrast to most solid tumors, the majority (72%) of de novo glioblastoma (GBM) retain a wild-type Tp53 gene while undergoing loss of CDKN2A (INK4a/Arf locus). Remarkably, transcriptional and proteomic data suggest that Tp53 is abundantly expressed in de novo GBM; however, it appears not to confer any survival advantage. The possibility that wild-type Tp53-expressing cells do not contribute to tumor growth seems unlikely since Tp53 is even more expressed in a paired analysis of initial and recurrent GBM. Taken together, these observations raise the possibility that the canonical Tp53 signaling may be functionally inactive in de novo GBM. Using primary cultures of conditional murine CDKN2A/B neural stem cells (NSC) and astrocytes we found that wild-type Tp53 is abundantly expressed following sequential loss of p16, p15 and p19 in astrocytes but not NSC. Astrocytes that lack both INK4a/b/Arf andTp53 show no growth advantage over INK4a/b/Arf -/- alone. Stable overexpression of Tp53 impairs proliferation of INK4a/b/Arf -/- NSC but not astrocytes, raising the intriguing possibility that inactivation of Tp53 signaling is cell type-specific. Furthermore, using Nutlin our data suggests that the Tp53-MDM2 axis is functional only in NSC but not astrocytes. Analysis of post-translational modifications (PTM) of Tp53 protein in INK4a/b/Arf -/- astrocytes and NSC reveals that it is entirely unacetylated in the former but not in the latter. Similarly, Tp53 expressed in primary GBM cells and patient-derived xenografts is also unacetylated. Consistent with this PTM, we found that SIRT1 is highly expressed in INK4a/b/Arf -/- astrocytes and not NSC and that inhibition of SIRT1 restores Tp53 acetylation, reduces cell proliferation and tumor growth. Mechanistic studies suggest that SIRT1 inhibition restores expression of Tp53 target genes (p21, PUMA, BAX). Taken together, our results identify a previously unrecognized cell type-specific PTM that inactivates Tp53 and provide a rationale for SIRT1 inhibition to restore Tp53 function.